2003
DOI: 10.1079/ssr2003132
|View full text |Cite
|
Sign up to set email alerts
|

Distinct expression patterns of β-1,3-glucanases and chitinases during the germination of Solanaceous seeds

Abstract: The expression patterns of ␤-1,3-glucanases (␤Glu) and chitinases (Chn) were investigated during the seed germination of members of the Cestroideae (three Nicotiana species, Petunia hybrida) and the Solanoideae (Capsicum annuum, Physalis peruviana) subgroups of Solanaceous species. Rupture of the micropylar testa (seed coat) and rupture of the micropylar endosperm, i.e. radicle emergence, were distinct and temporally separate events during the germination of Cestroideaetype seeds. ␤Glu accumulation in imbibed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 55 publications
0
50
0
2
Order By: Relevance
“…ABA inhibits the induction of bGlu I in the micropylar endosperm just before its rupture but does not affect testa rupture of tobacco. ABA also inhibits endosperm rupture, but not testa rupture, of several other Nicotiana species and of petunia (Petunia hybrida; Grappin et al, 2000;Krock et al, 2002;Petruzzelli et al, 2003;Schwachtje and Baldwin, 2004). Transgenic TKSG7 tobacco seeds overexpress bGlu I in the seed-covering layers under the control of a chimeric ABA-inducible transgene promoter (Leubner-Metzger, 2003).…”
mentioning
confidence: 99%
“…ABA inhibits the induction of bGlu I in the micropylar endosperm just before its rupture but does not affect testa rupture of tobacco. ABA also inhibits endosperm rupture, but not testa rupture, of several other Nicotiana species and of petunia (Petunia hybrida; Grappin et al, 2000;Krock et al, 2002;Petruzzelli et al, 2003;Schwachtje and Baldwin, 2004). Transgenic TKSG7 tobacco seeds overexpress bGlu I in the seed-covering layers under the control of a chimeric ABA-inducible transgene promoter (Leubner-Metzger, 2003).…”
mentioning
confidence: 99%
“…In contrast, endo-β-1,4-mannanase in tomato seeds is associated with the first phase of endosperm weakening and is not inhibited by ABA (Nonogaki et al, 2000;Toorop et al, 2000). Expression of endo-β-1, 3-glucanase in the micropylar endosperm, its inhibition by ABA and the inhibition of endosperm rupture by ABA is widespread among the Solanaceae (Wu et al, 2000;Leubner-Metzger, 2003;Petruzzelli et al, 2003). The ABA inhibition of endosperm rupture is partially reverted in transgenic tobacco seeds that overexpress endo-β-1,3-glucanase in the seed-covering layers under the control of an ABA-inducible transgene promoter LeubnerMetzger, 2002;Manz et al, 2005).…”
Section: Aba Endosperm Hydrolases and Endosperm Weakening In Establimentioning
confidence: 99%
“…Another phenomenon of endospermic seeds is that endosperm rupture is inhibited by ABA (Karssen, 1976;Finch-Savage and McQuistan, 1991;Toorop et al, 2000;Petruzzelli et al, 2003). In the established model systems of the asterid clade it has been shown that ABA inhibits endosperm rupture, at least in part, by acting in an inhibitory manner on the micropylar endosperm (Ni and Bradford, 1993;LeubnerMetzger, 2003;da Silva et al, 2004).…”
Section: Aba Inhibition Of Seed Germination: Aba Inhibits Endosperm Rmentioning
confidence: 99%
See 2 more Smart Citations